COLLABORATION AMONG LOCAL GOVERNMENT INSTITUTIONS IN ACHIEVING PUBLIC INFORMATION OPENNESS - RozidatenoPutri Hanida; Bimbi Irawan; Syamsurizaldi; Rahmatika Syaufi (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2018)
Open Government is one of the main roads for accelerating development and ensuring sustainable development.One of the strategies to encourage open government is by implementing what is the mandate of the Law on public information openness well.For citizens, this law means a guarantee to citizens to obtain public information in order to increase their active role in governance.As for government institutions, the law provides the obligation to government institutions to open access to public information, actively (without preceded by the request), and passively (with the request by the requestor) to the community.However, when citizens try to access the public information, it is not uncommon for the answer to be obtained is "This is the system", "The procedure is like this", "I am not authorized".This is the background of research on how collaboration among local government institutions in Padang Panjang Municipality in realizing public information openness.With qualitative descriptive method, through the analysis of data in ethics and emic found that Local Government of Padang Panjang Municipality developed collaboration among government institutions that marked by the cooperation, interaction, compromise of some related elements to encourage public information openness.One of the ways implemented by Local Government of Padang Panjang Municipality is by the establishment of Management Officer of Information and Documentation or Pejabat Pengelola Informasi dan Dokumentasi (PPID) or consisting of Main PPID (PPID Utama) and Asssisytance PPID (PPID Pembantu).For the future, it is required a clear Standard Operating Procedure for the local government work unit to network each other in encouraging the openness of public information, so the impression that the responsibility of creating public information openness in Padang Panjang Municipality is only a function of PPID can be eliminated.